HUBUNGAN CORE STABILITY DENGAN ENDURANCE DAN BALANCE PADA PEMAIN SEPAKBOLA CLUB PSPS PASAR SURANTIH - Ibadurrahman; Donal Syafrianto; Didin Tohidin; Windo Wiria Dinata (Jurnal IKEOR, 2023)
The problem in this study is that many of the players have poor endurance and balance, this is indicated by when the players do training, sparring tests and also during official matches. Such as the lack of some physical condition training applied to PSPS Surantih players. This study aims to determine the relationship between cote stability and endurance and balance in the PSPS football club player Surantih market. This research is a type of correlational research. The population in this study was all 30 PSR futsal athletes in Padang. The sampling technique in this study is a purposive sample technique, so that a sample of 20 people was obtained. Data collection using McGill's Core Endurance test to measure core stability, Data collection using McGill's Core Endurance test to measure core stability, bleep test to measure endurance and Star excursion balance test to measure balance as the target data is processed with statistics. Based on the calculation of statistical test results, the results of the study found that there is a significant relationship between core stability and endurance, which is 35.5% and the relationship between core stability and balance, which is 53.8%.